22-4(3-x)=42

Simple and best practice solution for 22-4(3-x)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22-4(3-x)=42 equation:


Simplifying
22 + -4(3 + -1x) = 42
22 + (3 * -4 + -1x * -4) = 42
22 + (-12 + 4x) = 42

Combine like terms: 22 + -12 = 10
10 + 4x = 42

Solving
10 + 4x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 4x = 42 + -10

Combine like terms: 10 + -10 = 0
0 + 4x = 42 + -10
4x = 42 + -10

Combine like terms: 42 + -10 = 32
4x = 32

Divide each side by '4'.
x = 8

Simplifying
x = 8

See similar equations:

| 36=(x+3)(x+3) | | 2x^2-10-x=0 | | 0.6x+4=20-x | | 0.6+4=20-x | | 12-w=157 | | 260-w=145 | | -4(b-3)=-44 | | 195=-x+1 | | 36=2x^2+6x+9 | | 4p-31+p+13=P+50 | | 3=-6v+3(v+8) | | -3(z+2)=24 | | 2n^2+n-36=0 | | x+3x+5=12 | | -2(c-1)=18 | | 4x^2+39x+171=0 | | w+12+2w+2=w+50 | | 2.5x-6=-4-3.5 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | x^2+y^2-2x-8y-47=0 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | 15x-48+5x=13x | | (x+4)2+(y+4)2=32 | | xcubed-2xsquared+1=0 | | x-2y=28 | | 6=2-8(1-y) | | (x-5)2+(y-5)2=27 | | xcubed-2quared+1=0 | | 44+q+41=8q+28 | | (x+2)2+y^2=100 | | 2w-5+33=w+48 | | y^2-7y-60=0 |

Equations solver categories